Upaya Meningkatkan Hasil Belajar IPA Melalui Metode Pembelajaran Discovery Terbimbing pada Siswa Kelas V SD Negeri 01 Durian Tinggi Kecamatan Kapur IX - Asnawati Asnawati (Pendidikan Biologi FKIP UMMY, 2019)
This study aims to improve the learning outcomes of science students in grade V SD Negeri 01 Durian Tinggi District Kapur IX using discovery-guided learning methods. This type of research is classroom action research. The subjects of this study were the fifth grade students of SD Negeri 01 Durian Tinggi, totaling 17 students, consisting of 3 male students and 14 female students. Researchers used action research models from Kemmis and Taggart. This research was conducted in two cycles of action. Each cycle is carried out in two meetings. In each cycle there are planning, implementing, observing, and reflecting activities. The instruments used were observation sheets and tests. Observation data were analyzed descriptively qualitatively while test results were analyzed descriptively quantitative percentages. Initial test results on the pre-cycle percentage of students whose grades are above the KKM which reached 23.53%. The results of the first cycle showed that the percentage of students whose grades were above KKM had only reached 64.71%, so that it still could not reach the criteria of research success. In cycle II, the steps in applying discovery learning methods to improve student success are done by providing motivation, dividing the number of smaller group members and heterogeneous members, and providing opportunities for group presentations on the results of practicum in front of the class. The percentage of student grades above the KKM in the second cycle increased to 100%. Based on the results of the study, it can be seen that the guided discovey method is able to improve the science learning outcomes.